2022
DOI: 10.3390/recycling7020025
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of Pretreated Polyolefin-Based Ocean-Bound Plastic Waste by Incorporating Clay and Rubber

Abstract: Plastic waste found in oceans has become a major concern because of its impact on marine organisms and human health. There is significant global interest in recycling these materials, but their reclamation, sorting, cleaning, and reprocessing, along with the degradation that occurs in the natural environment, all make it difficult to achieve high quality recycled resins from ocean plastic waste. To mitigate these limitations, various additives including clay and rubber were explored. In this study, we compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…It was found that the 3D printed R-HDPE/ R-PP (70:30) blend alone shows 34% improvement in Young’s modulus, while the addition of 20% bio-carbon in the blend shows improvement by 11–15% in the mechanical properties. Martey et al [ 71 ] compounded ocean-bound waste (o-HDPE and o-PP), virgin polymer (low-density polyethylene (LDPE) and polystyrene (PS)) with functionalized clay, styrene multi-block-copolymer (SMB) and ethylene–propylene-based rubber (EPR) additives. It was observed that adding clay particles to the polymer matrix creates a rough surface and causes brittleness in the final material.…”
Section: Use Of Additivesmentioning
confidence: 99%
See 4 more Smart Citations
“…It was found that the 3D printed R-HDPE/ R-PP (70:30) blend alone shows 34% improvement in Young’s modulus, while the addition of 20% bio-carbon in the blend shows improvement by 11–15% in the mechanical properties. Martey et al [ 71 ] compounded ocean-bound waste (o-HDPE and o-PP), virgin polymer (low-density polyethylene (LDPE) and polystyrene (PS)) with functionalized clay, styrene multi-block-copolymer (SMB) and ethylene–propylene-based rubber (EPR) additives. It was observed that adding clay particles to the polymer matrix creates a rough surface and causes brittleness in the final material.…”
Section: Use Of Additivesmentioning
confidence: 99%
“…It was observed that adding clay particles to the polymer matrix creates a rough surface and causes brittleness in the final material. At the same time, incorporating EPR and rubber in the polymer significantly enhances the elasticity and mechanical performance of the composite [ 71 ]. SEM images of fractured surfaces in Fig.…”
Section: Use Of Additivesmentioning
confidence: 99%
See 3 more Smart Citations